1998
DOI: 10.1038/sj.gt.3300617
|View full text |Cite
|
Sign up to set email alerts
|

Persistent gene expression in rat liver in vivo by repetitive transfections using HVJ-liposome

Abstract: Most viral vectors are highly immunogenic and are of limthirds of the liver by histological staining. It was found that ited use for somatic gene therapy that requires repetitive the transfection efficiency was not affected by repetitive administrations. We have developed a highly efficient gene transfections. In support of these findings, antibody transduction procedure useful for repetitive transfections response to HVJ-liposome detected in the rat sera was using liposome containing hemagglutinating virus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 19 publications
1
47
0
Order By: Relevance
“…22 Thus, HVJ-liposome appears to be safe for myocytes, holding promise for the clinical application of this method.…”
Section: Figure 6 Neither Hvj Group (A) Nor Control Group (B) Showed mentioning
confidence: 99%
See 1 more Smart Citation
“…22 Thus, HVJ-liposome appears to be safe for myocytes, holding promise for the clinical application of this method.…”
Section: Figure 6 Neither Hvj Group (A) Nor Control Group (B) Showed mentioning
confidence: 99%
“…They speculated that the structural characteristics of HVJ-liposomes, such as being soft and flexible, caused the increase in permeability through the intracellular junctions among the endothelial cells. 22 Thus, it is apparent that HVJ-liposome can migrate through the vessel walls and reach the nuclei of myocytes. No other vectors have been reported to be useful for transmigration of genes without significant damage when administered through coronary arteries.…”
Section: Figure 6 Neither Hvj Group (A) Nor Control Group (B) Showed mentioning
confidence: 99%
“…Among the many approaches for gene transfer in vivo using viral or nonviral vectors, the HVJ-liposome method is thought to be the most suitable for antiangiogenic gene therapy because HVJ-liposomes can maintain gene expression for long periods by repeated injection, without apparent toxicity, inflammation or significant immunogenicity in vivo. [31][32][33][34] Although the transfection efficiency of HVJ-liposomes is relatively lower than that of viral vectors such as adenoviral vectors, repeated transductions with HVJliposomes make it feasible to express continuously an indicated gene, and thus may be more advantageous for antiangiogenic therapy against cancer. Boehm et al 35 reported that cyclical therapy with the antiangiogenic proteins, angiostatin and endostatin, resulted in permanent tumor arrest at a microscope dormant size with blocked angiogenesis, even after the therapy was discontinued.…”
Section: Resultsmentioning
confidence: 99%
“…11 Recently, we demonstrated that repetitive gene transfer can be achieved by HVJ-liposome vector system without side-effects or neutralization of the delivery system. 12 In our previous studies we demonstrated that when pcDNA3 plasmid containing the human tumor antigen genes MAGE-1 and MAGE-3 were encapsulated in HVJ-liposomes and injected into mice intramuscularly, there were no side-effects and there was highly efficient transfection of muscle cells for several weeks. 11 Recently, we improved the HVJ-liposome system for more efficient gene delivery by changing the lipid components of the liposomes, and developed a novel HVJ-AVE (artificial viral envelope) liposome which increased gene expression in mouse skeletal muscle and liver five to 10 times higher compared with conventional HVJliposomes.…”
Section: Introductionmentioning
confidence: 97%